PERBANDINGAN METODE LZ77, METODE HUFFMAN DAN METODE DEFLATE TERHADAP KOMPRESI DATA TEKS - Christian Puji Nugraha; R. Gunawan Santosa; Lukas Chrisantyo A.A. (Jurnal Informatika, 2015)
Data compression is a very important process in the world that has been vastly using digital files, such as for texts, images, sounds or videos. Those digital files has a varied size and often taking disk storage spaces. To overcome this problem, many experts created compression algorithms, both for lossy and lossless compression. This research discusses about testing of four lossless compression algorithms that applied for text files, such as LZ77, Static Huffman, LZ77 combined with Static Huffman, and Deflate. Performance comparison of the four algorithms is measured by obtaining the compression ratio. From the test results can be concluded that the Deflate algorithm is the best algorithm due to the use of multiple modes, i.e. uncompressed mode, LZ77 combined with Static Huffman mode, and LZ77 combined with Dynamic Huffman Coding mode. The results also showed that the Deflate algorithm can compress text files and generates an average compression ratio of 38.84%.